Exploring the other side of innovative managerial decision-making: Emotions - Anna-Maria Kanzola; Konstantina Papaioannou; Panagiōtēs E. Petrakēs (Journal of Innovation & Knowledge (JIK), 2024)
The strict rational paradigm of neoclassical economic theory has resulted in limited exploration of emotions in managerial decision-making processes. This study attempts to address this gap by examining how emotions influence efficient managerial decision-making, generating a modern perspective for organizational theory beyond the existing theoretical paradigm. The concept of managerial decision-making is approached through three dependent variables: strategic planning, innovative crisis management, and pragmatism. This study analyzed the responses of 151 managers of small- and medium-sized firms in Greece collected during field research in 2023. Emotions are perceived as unique information that interacts with other factors, such as the conscious evaluation of inputs. The analysis of emotions was based on a modified understanding of the anthropological term of emotional culture. The findings demonstrate that emotional culture contributes to managerial decision-making. Influential variables included basic emotions, emotions that communicate motives, cultural values, fast and slow thinking, and demographics. These variables highlight the interaction of pure emotional and rational factors in managerial decision-making. This study provides insights into how 'human-related' traits contribute to or affect decision-making processes. This interdisciplinary perspective has both micro- and macro-level implications. At the micro level, the study explores strategic management, managerial skills for effective decision-making - especially considering the rise of artificial intelligence - and modern perspectives of organizational theory based on behavioral economics. At the macro level, it offers insights into cumulative behavioral expressions and how emotion analysis could be used to understand cultures and stereotypes within societies. The study has implications for the relationship between policymaking and production structure.
Keywords: D90; D91; H12; Z10; 650; Efficient managerial decision-making; Emotional culture; Emotions; Innovation; Type 1 and Type 2 thinking; Risk-aversion